Greenland, valley and streams at Kjerulf Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end of Main Valley. Distant background shows Left Valley with its stream descending the right side. Background on right shows L.A.B.'s Curry-comb Peak forming western side of Left Valley. Foreground: Streams of Right and Left Valleys. Photo taken looking S.S.E.